Plasma electrolytic oxidation of binary Mg-Al and Mg-Zn alloys - Gunduz, K. O.; Oter, Z. C.; Tarakci, M.; Gencer, Y. (Elsevier Science Sa, 2017)
In this study the effect of aluminum and zinc addition on the plasma electrolytic oxidation (PEO) behavior of pure magnesium was investigated. Firstly, binary alloys of Mg-Al and Mg-Zn containing atomically 2, 4 and 8% were produced via induction melting. These alloys were than coated in a silicate based electrolyte at 120 min employing an asymmetrical AC power source with a frequency of 50 Hz and characterized by scanning electron microscope-energy dispersive spectroscopy (SEM-EDS), X-ray diffraction (XRD) and microhardness tester. Obtained results indicated that compared to PEO of pure magnesium, addition of aluminum into magnesium resulted in a wavy substrate/coating interface, retarded the growth rate and increased microhardness. The addition of zinc into magnesium also retarded the coating growth rate, though not as significantly as aluminum; however, bright precipitates as a continuous part of the substrate were observed in the compact region of the coatings around which oxidation was hindered. No extra phases other than Forsterite and Periclase were found according to the XRD results although some pits in the inner region which might be a mixture of MgO-Al2O3 were detected by cross-sectional SEM-EDS studies. SEM-EDS results also showed that aluminum was incorporated both in outer and inner region of the coatings while zinc was only detected on the regions consisted of bright precipitates in the inner region of the coatings. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Plasma electrolytic oxidation; Magnesium; Alloying element; Aluminum; Zinc; Coating